Properties of the non-catalytic nucleotide site of the Ca²⁺-ATPase of sarcoplasmic reticulum - Davidson, George Alexander (Division of Chemical Pathology, 2018)
Properties of the regulatory nucleotide binding site of the Ca²⁺-ATPase of skeletal muscle sarcoplasmic reticulum have been investigated. Previously, several lines of evidence have indicated the existence of both catalytic and regulatory nucleotide binding sites on the same polypeptide species. The present study concentrates on the interaction of the ATP analogue, 2'-3'-0-(2,4,6-trinitrocyclohexadienylidine) adenosine 5'-triphosphate, (TNP-ATP), with sites on the non-phosphorylated and phosphorylated enzyme. In particular those conformational transitions linking TNP-ATP fluorescence to the phosphoenzyme subspecies have been sought. Previous studies have demonstrated a close relationship between TNP-ATP fluorescence and phosphoenzyme formed from ATP plus Ca²⁺, or from inorganic phosphate (Pi) in the absence of Ca²⁺, in the reverse direction of the cycle. However, the precise relationship of TNP-ATP fluorescence to the energy transducing conformations of the ATPase is controversial. TNP-ATP binding was investigated by spectrophotometric methods and by the synthesis of [ ¹⁴C] TNP-ATP. [ ¹⁴C] TNP-ATP bound to the ATPase site with high affinity ([TNP-ATP] 0. 5 = 0.12 uM), and · a stoichiometry of 5.4 nmol/mg. [ ¹⁴C] ATP binding stoichiometry was 6.1 nmol/mg, demonstrating that TNP-ATP binds to a single family of sites. The nature of the phosphoenzyme intermediate species that results in enhanced TNP-ATP fluorescence was investigated. NEM derivitization, Sr²⁺-transport and Ca²⁺-oxalate uptake have previously been found to alter the distribution or relative levels of phosphoenzyme intermediates. Modification of thiol groups responsible for phosphoenzyme decomposition (SHd), using N-ethylmaleimide (NEM) (0.4 mM) with 50 uM Ca²⁺, 1 mM AMP-PNP at pH 7.0, resulted in a 50% decrease in Ca²⁺-uptake, Ca²⁺-ATPase activity and ADP-insensitive E-P (E₂-P), while total EP (E₁-P + E₂-P = 3.2 nmol/mg), remained unaltered. ATP-dependent TNP-ATP enhanced fluorescence decreased by 50% under these conditions. Ca²⁺-oxalate induced turnover has previously been shown to decrease steady-state E₂-P levels by prevention of Ca²⁺ gradient formation. Oxalate (5 mM) caused a 40% decrease in ATP-induced TNP-ATP fluorescence levels while total EP levels remained relatively unaltered. Previous studies have shown that Sr²⁺-induced turnover favours higher levels of E₂-P by inhibiting the reverse reaction from E₂-P to E₁-P. Strontium-induced turnover increased TNP-ATP fluorescence by 10% as compared to that of Ca²⁺, without affecting steady-state E-P levels, consistent with an E₂-P conformation relationship to enhanced TNP-ATP fluorescence. The binding site for TNP-ATP on the enzyme was investigated by chase studies using millimolar concentrations of nucleotides. ATP and ADP diminished TNP-ATP fluorescence competitively, with apparent Km values of 1.25 and 0.54 mM respectively, consistent with their affinities of binding to the regulatory site. The rates of decrease of fluorescence (25 and 34 sec⁻¹ at 5 ᵒC, respectively), were of the same order of magnitude as the derived "off" rate of TNP-ATP from the site of enhanced fluorescence (33 sec⁻¹), consistent with TNP-ATP being bound to the regulatory site of the enzyme. Enhanced TNP-ATP fluorescence has previously been related to decreased water activity of the probe site. Alteration of water activity by structure- forming (Deuterium oxide) and structure-breaking solutes (KSCN) in relation to fluorescence were explored. Replacement of H₂O by D₂O altered the fluorescence of unbound TNP-ATP. The apparent for TNP-ATP binding to the E₂-P conformation of the regulatory site. The regulatory site appears to be a modified form of the phosphorylated catalytic site. It is proposed that TNP-ATP fluorescence monitors an enzyme conformation related to Ca²⁺ binding to an inward oriented site of low affinity. The mechanism of K⁺ fluorescence quenching appears to be via an acceleration of dephosphorylation, as opposed to a change in affinity of the enzyme for TNP-ATP, as previously suggested. The K⁺ sensitivity of TNP-ATP fluorescence has proved useful in demonstrating a direct interaction of valinomycin with the enzyme through the monovalent cation binding site. Valinomycin appears to bind directly to the enzyme and to selectively accelerate the "off" rate of K⁺ from this site.